Recent Challenges of Proper Implementation of Panchayati Raj in Haryana: Exploring the Challenges and Suggested Measures for Effective Implementation of Panchayati Raj in Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Panchayati raj in Haryana is known as the system of rural local self-government. The Panchayati Raj system has been established in all the states of India including Haryana state, by the Acts of the state legislatures to build democracy at the grassroots level. It is related to rural development. It was constitutionalised through the 73rd constitutional Amendment Act of 1992 in India and in Haryana it is constitutionalised through Panchayati Raj Act, 1994 (Act Number 11 of 1994). Panchayati raj institutions provide opportunities to the citizens to participate in the political and development process at grassroots level. But still Panchayati raj institutions are not working properly particularly in Haryana state of India. The present paper studies the challenges of Panchayati raj institutions in Haryana and tries to provide suggestions and measures to effectively reducing of problems, facing the all challenges.